Effects of ketamine and propofol on muscarinic plateau potentials in rat neocortical pyramidal cells - Anne S. Fleiner; Daniel Kolnier; Nicholas Hagger-Vaughan; Johan Ræder; Johan F. Storm (PLoS ONE, 2025)
Propofol and ketamine are widely used general anaesthetics, but have different effects on consciousness: propofol gives a deeply unconscious state, with little or no dream reports, whereas vivid dreams are often reported after ketamine anaesthesia. Ketamine is an N-methyl-D-aspartate (NMDA) receptor antagonist, while propofol is a γ-aminobutyric-acid (GABAA) receptor positive allosteric modulator, but these mechanisms do not fully explain how these drugs alter consciousness. Most previous in vitro studies of cellular mechanisms of anaesthetics have used brain slices or neurons in a nearly “comatose” state, because no “arousing” neuromodulators were added. Here we tested mechanisms of anaesthetics in rat medial prefrontal cortex (mPFC) slices after bath-applying the cholinergic agonist muscarine to partly mimic an “aroused-like” state, using whole-cell patch-clamp recordings from layer 2/3 pyramidal cells (L2/3PCs). According to leading theories of access consciousness and working memory, L2/3PCs are particularly important for these cognitive functions. We found that muscarine induced long-lasting depolarising plateau potentials (PPs) and spiking following brief depolarising current injections in the L2/3PCs. After 2 hours of pre-incubation with ketamine or propofol, the muscarine-induced PPs were altered in seemingly different ways: 3 μM propofol reduced the PPs and (significantly) spiking, whereas 20 μM ketamine seemed to enhance PPs and spiking (non-significantly). Brief wash-in of these drug concentrations failed to induce such effects, probably due to insufficient equilibration by diffusion in the slices. In contrast, pre-incubation with a high dose (100 μM) of ketamine suppressed the PPs and spiking. We discuss whether the apparently different effects on PPs may possibly be related to contrasting clinical effects: ketamine causing atypical anaesthesia with vivid, “psychedelic” dreaming while propofol causes less dreaming.